Peningkatan Pemberdayaan Penyandang Tunanetra melalui Perancangan Social Media Newsletter di Yayasan Sosial Tunanetra - Imran, Maharani (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
In 2023, the number of blind people with disabilities in Indonesia reached 1.5 percent of the total population of Indonesia, which is about 4 million people. Social media newsletters can be used as fundraising media and information media for activities or programs conducted by the Foundation for Blind People. This charitable activity aims to support and empower blind people, especially those who are in poor, orphaned or neglected circumstances. The collaboration between the charitable team and the foundation has resulted in a social media newsletter that is not only visually appealing but also informative. It is important to maintain the sustainability of this activity, especially in digital form, to ensure that the latest information can be quickly accessed by the wider community.